Screening of yard long bean genotypes for resistance to legume pod borer, Maruca vitrata F.: Screening of yard long bean genotypes (Journal of the Bangladesh Agricultural University, 2018)
The research work on the evaluation of yard long bean genotypes for resistance to legume pod borer, Maruca vitrata F. was carried out in two consecutive seasons viz., kharif 2015 and rabi 2015-16 in randomized complete block design (RCBD) in the field of the Department of Entomology, Bangladesh Agricultural University (BAU), Mymensingh and chemical analysis of sugar, protein and phenol of yard long bean were carried out at Bangladesh Institute of Nuclear Agriculture (BINA), Professor Mohammad Hossain Central Laboratory and laboratory of the Department of Biochemistry and Molecularbiology, Bangladesh Agricultural University (BAU), Mymensingh. Nine genotypes of yard long bean were evaluated and reacted distinctly to M. vitrata with significantly different levels of infestation to flowers, pods and yield. The genotype Long Red Mollika was categorized as moderately resistant to legume pod borer in both kharif and rabi seasons. Genotype YL 305 was found susceptible in both the seasons. The plant attributes, both vegetative and reproductive, of yard long bean did not show any significant correlation in favour of resistance to M. vitrata. Yard long bean genotypes also did not show resistant reaction to M. vitrata in respect of sugar and phenol but particularly protein showed antibiosis against M. vitrata.J. Bangladesh Agril. Univ. 16(3): 424–428, December 2018